1986
DOI: 10.1037/0012-1649.22.3.317
|View full text |Cite
|
Sign up to set email alerts
|

Family socialization and the IQ test performance of traditionally and transracially adopted Black children.

Abstract: The purpose of this research was to investigate the efficacy of the difference orientation for interpreting black children's lower average intelligence test performance. This study examines the response styles to cognitive demands of the Wechsler Intelligence Scale for Children (WISC) exhibited by two groups of adopted black children, aged from 7 to 10 years at the time of testing, and their average IQ. One group had been adopted by middle-class white families (i.e., transracially adopted), and the second grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 33 publications
1
32
0
4
Order By: Relevance
“…However, researchers have asserted that children are strongly influenced by their environment and the values stressed by the cultural group to which they belong. These values may impact on developmental evaluation scores (Anastasi, 1988;Boykin, 1983;Harkness & Super, 1993;Moore, 1986;Sattler, 1988;Rogoff, 1990). More recently, Garcia Coll (1990) and colleagues (Garcia Coll, Lamberty, Jenkins, Pipes McAdoo, Crnic, Wasik, & Vasquez-Garcia, 1996) have argued that developmental pathways for children of minority status have not been thoroughly examined.…”
Section: Developmental Scores On the Denver-ii And Bayley-iimentioning
confidence: 97%
See 1 more Smart Citation
“…However, researchers have asserted that children are strongly influenced by their environment and the values stressed by the cultural group to which they belong. These values may impact on developmental evaluation scores (Anastasi, 1988;Boykin, 1983;Harkness & Super, 1993;Moore, 1986;Sattler, 1988;Rogoff, 1990). More recently, Garcia Coll (1990) and colleagues (Garcia Coll, Lamberty, Jenkins, Pipes McAdoo, Crnic, Wasik, & Vasquez-Garcia, 1996) have argued that developmental pathways for children of minority status have not been thoroughly examined.…”
Section: Developmental Scores On the Denver-ii And Bayley-iimentioning
confidence: 97%
“…Caregivers of children may have inappropriate expectations for these children's emotional, cognitive, and physical capabilities (Coyne & Brown, 1985, 1986Schilling, Kirkham, & Schinke, 1986). Training programs should address the developmental needs of children across domains, and should target all types of caregivers, including parents, kin, and nonrelative caregivers.…”
Section: Policy Implicationsmentioning
confidence: 98%
“…In two studies of 2-to 5-year-olds raised in English residential nurseries, Tizard (1974) compared Black (African and West Indian), White, and mixed-parentage children and found no significant differences among the three groups on several language comprehension tests and on the Wechsler Preschool and Primary Scale of Intelligence (WPPSI); the single significant difference was in favor of the non-White children. Moore (1986) found that at age 7, 23 Black children adopted by middle-class White families had a mean IQ of 117, whereas a similar group of children adopted by middle-class Black families had a mean IQ of 104, both significantly above the national Black mean of 85. To be more informative, future studies need to be supplemented by follow-up testing, as in the Minnesota Study.…”
Section: Section 2: the Two Conflicting Research Programsmentioning
confidence: 99%
“…These studies have been generally dismissed due to very small samples, and typically have examined class rather than race differences (Schiff et al 1978). A similar line of research that uses much larger samples is Elsie Moore's (1986) analysis of differences between Black children adopted into middle-class White homes and Black children adopted into middle-class Black homes.…”
Section: Geneticsmentioning
confidence: 99%